Factors associated with gestational diabetes mellitus among pregnant women in the Klang Valley, Malaysia - Thilliampalam, Deepa (2022)
Diet and lifestyle were consistently linked with gestational diabetes mellitus (GDM) over the year. With multiple interventions, nutritional policies and campaign the prevalence of GDM still accelerating over the year. This highlights the need of different dietary approach to prevent and manage this disease. The current study aimed to study the factors associated with GDM among pregnant women. In addition, other dietary factors such as body adiposity, dietary energy, macronutrients, micronutrients, diet quality as well as physical activity were also assessed in relation to GDM. This is a case control study conducted among 264 samples (146 GDM subjects and 188 non GDM subjects) in selected health clinic in Klang Valley. A structure questionnaire was used to collect the data. The height and weight of study subjects were assessed to determine their body mass index. All the data was analysed using SPSS version 23. As age increases per year the probability to develop GDM increased by 15% among study subjects (AOR = 1.15, 95% CI = 1.07 – 1.23, p < 0.001). Study subjects who were 30 years old and above were more likely to develop GDM more than two-fold (AOR = 2.60, 95% CI = 1.53 – 4.43, p< 0.001). Compared to those with tertiary educational background (university), study subjects with secondary school background most likely to be diagnosed with GDM (AOR = 11.6, 95% CI = 4.40 – 30.9, p < 0.001) followed by those from high school/ college (AOR = 9.52, 95% CI = 3.90 – 23.2, p < 0.001). Compared to study subjects with lowest household income (< RM1000), those with higher household income (> RM 4000) were more likely to be diagnosed with GDM (AOR = 16.52, 95% CI = 3.30 – 82.71, p = 0.001). As BMI increases by 1kg/m2 the probability to develop GDM increased by 9% among study subjects (AOR = 1.09, 95% CI = 1.01 – 1.18, p =0.030). Compared to study subjects with BMI below than 25.0kg/m2, those who were overweight or obese were twice more likely to be diagnosed with GDM (AOR = 2.10, 95% CI = 1.07-4.09, p = 0.029). As dietary energy increases per 1kcal the probability to develop GDM increased by 46% among study subjects (COR = 1.46, 95% CI = 1.12- 1.90, p = 0.005). As carbohydrate consumption increases per 1g the probability to develop GDM increased by 63% among study subjects (AOR = 1.63, 1.12 – 2.36, p = 0.011). As calorie from carbohydrate increases per 1kcal the probability to develop GDM increased by 48% among study subjects (AOR = 1.48, 95% CI = 1.04 – 2.12, p = 0.031). As calories from protein and fat increases per 1kcal the probability to develop GDM reduced by 40% and 32% respectively among (AOR = 0.60, 95% CI = 0.42-0.85, p = 0.005 and AOR = 0.68, 95% CI = 0.48 – 0.97, p = 0.033). As calcium and saturated fat increases per 1mg and 1 g, the probability to develop GDM increased by 66% and 46% among study subjects (AOR = 1.66, 95% CI = 1.09 – 2.52, p = 0.018 and AOR = 1.45, 95% CI = 1.01 - 2.09, p = 0.047). The highest tertile (T3) of PRAL showed a significant association with GDM among study subjects (COR = 2.11, 95% CI =1.15-3.86, p = 0.016). As the frequency of acidic diet intake per day increases by 1 unit the probability to develop GDM increased by 2.63 times among study subjects (AOR = 2.63, 95% CI = 1.66-4.15, p< 0.001). Adherence to acidic diet was more likely to increase the odds to be diagnosed with GDM among study subjects (AOR = 8.51, 95% CI = 3.95 – 18.3, p < 0.001). Study subjects who adhere to cereals, cereal products and tubers intake recommendation have an increased odd of GDM (AOR = 40.54, 95% CI = 5.77 – 284.9, p < 0.001). Adherence to whole grain cereal intake recommendation significantly reduced the odd of GDM (AOR = 0.012, 95% CI = 0.001 – 0.20. p = 0.002). On the other hand, adherence to legume and their products intake recommendation was significantly reduced the odd of GDM by 83% (AOR = 0.17, 95% CI = 0.03, 0.81, p = 0.026). High diet quality (Q4) was found significantly reduced the odd of GDM by 75% (AOR = 0.25, 95% CI = 0.09 - 0.65, p = 0.004). Eight variables were selected against GDM among pregnant women as the important variables in the final model which were age, educational background, monthly household income, frequency of acidic diet intake per day, acidic diet adherence, calorie from protein, adherence to cereals, cereal products and tubers intake, and adherence to legume and their product. Hence, in preventing GDM among pregnant mother, nutritionists, dietitians, clinicians, ministries and policy makers can start a routine intervention by providing holistic support for those who have these associated factors to help them cope with these important factors and to improve the goal of achieving a good glucose level and other further complications.